STRATEGI PEMASARAN LA TERA COFFEE SHOP DALAM MENGHADAPI MARAKNYA COFFEE SHOP DI KOTA JAMBI - Ivy Ravika Vuri; Muhamad Subhan (ICONS: Islamic Economics Journal, 2026)
This study aims to analyze the marketing strategies implemented by La Tera Coffee Shop in facing the intense competition in the coffee shop market in Jambi City. The study employed a qualitative descriptive method, with data collection techniques including interviews, observation, and documentation. The focus of the study was on the implementation of the marketing mix (7Ps), which includes product, price, place, promotion, physical evidence, people, and processes, to maintain business existence and attract customers. The results indicate that La Tera Coffee Shop has implemented a marketing strategy through product innovation, friendly service, informative promotions, social media utilization, and a customer loyalty program. This strategy has proven to support increased competitiveness amidst intense competition. However, weaknesses remain, such as suboptimal digital promotions and the need to improve service consistency. Overall, the marketing strategy implemented has made a positive contribution to maintaining customer loyalty and strengthening La Tera Coffee  Shop's position in the local market.